2021
DOI: 10.1021/acs.jchemed.1c00352
|View full text |Cite
|
Sign up to set email alerts
|

A QuantCrit Investigation of Society’s Educational Debts Due to Racism and Sexism in Chemistry Student Learning

Abstract: A QuantCrit investigation of society's educational debts due to racism and sexism in chemistry student learning. ChemRxiv. Preprint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 72 publications
1
25
1
Order By: Relevance
“…Differences or “gaps” in student performance or achievement measures between sexes and races/ethnicities have long been used to measure inequity, though there is a current movement away from the use of achievement or performance “gaps.” Eddy et al point out that women who attend college often come in with higher measures of academic preparation, such as higher average high school GPAs, and studies that compare averages of men and women will tend to not show gender differences and studies that compare students of equal preparation do show gender differences. Inequities between sexes have been found in foundational STEM courses and specifically in chemistry courses, , although observed differences vary by the achievement measure used, with women often earning higher scores in other coursework , (e.g., homework, laboratory) and men earning higher scores on exams. Further analyses have shown that differences in exam grades are affected by the contexts used to frame test questions, and the cognitive level and format of exams …”
Section: Literature Review Of Inequitymentioning
confidence: 99%
See 2 more Smart Citations
“…Differences or “gaps” in student performance or achievement measures between sexes and races/ethnicities have long been used to measure inequity, though there is a current movement away from the use of achievement or performance “gaps.” Eddy et al point out that women who attend college often come in with higher measures of academic preparation, such as higher average high school GPAs, and studies that compare averages of men and women will tend to not show gender differences and studies that compare students of equal preparation do show gender differences. Inequities between sexes have been found in foundational STEM courses and specifically in chemistry courses, , although observed differences vary by the achievement measure used, with women often earning higher scores in other coursework , (e.g., homework, laboratory) and men earning higher scores on exams. Further analyses have shown that differences in exam grades are affected by the contexts used to frame test questions, and the cognitive level and format of exams …”
Section: Literature Review Of Inequitymentioning
confidence: 99%
“…The design and implementation of more structured learning environments and the incorporation of teaching strategies that more actively engage students in the learning process seem to improve the academic performance of all students . Some studies have shown reforms can reduce inequities in college STEM courses, , while other investigations provided evidence that such reforms are not sufficient to create equity between sexes and all races/ethnicities. ,, …”
Section: Literature Review Of Inequitymentioning
confidence: 99%
See 1 more Smart Citation
“…Van Dusen and Nissen's (2020) decisions preserved statistical power for using variance explained for model selection. In later work (e.g., Nissen et al, 2021;Van Dusen et al, 2021), we focused on respecting students' identities first and following statistical guidance for minimum group sizes second. We used a minimum group size of 20 (Simmons et al, 2011) to include social identifier variables or interactions to minimize the chance of spurious results.…”
Section: Reflections On Handling Social Identifier Datamentioning
confidence: 99%
“…The shift to online examination serves as an opportunity to rethink assessment and curriculum more broadly. We want to emphasize that we disagree with deficit framing, whereby students are blamed for academic difficulties resulting from racist and sexist power structures, and we believe that the injustice of current academic systems 8 is at the root of student behaviours. Recent findings show that teaching focused on reasoning can reduce gaps in performance between marginalized groups in STEM compared with their privileged peers 9 .…”
mentioning
confidence: 95%